Formation of images by expressive meansof ballroom dance - Xingluan Wang (ХДАК, 2025)
The integration of traditional Chinese cultural elements into ballroom dance represents a fascinating intersection of art forms, reflecting the broader trends of globalization and cultural exchange. As ballroom dance evolves, there is a growing interest in incorporating diverse cultural influences to enhance its expressive potential. Traditional Chinese culture, with its rich history, intricate philosophies, and unique aesthetics, offers a wealth of inspiration for choreographers seeking to innovate within the realm of dance.
qualification work for obtaining master’s degree in specialty 024 Choreography
Keywords: хореографія бальна; бальні танці; ballroom dancing; хореографічне мистецтво Китаю